2020
DOI: 10.1080/24750263.2020.1716866
|View full text |Cite
|
Sign up to set email alerts
|

Relation between biometric parameters and autumn-winter food availability in a roe deer (Capreolus capreolus) population in central Italy

Abstract: The numerical increase of roe deer has resulted in a noticeable growth of hunting activities allowing to have a great availability of biometrical data from both the hunted samples and the population by describing trends and variations and, then, optimize the consequent wildlife management decisions. Specifically, we analyzed biometric data of a roe deer (Capreolus capreolus) population at the Macerata Province, in central Italy. We focused on two animal groups: fawns (<11 months old) and adults (>2 years old).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 23 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…In this study, we found that the conversion factor allowed us to get additional parameters which were inserted into the classical biometric database and then analyzed to obtain information about the wildlife population status. These parameters can be correlated with a lot of different features such as age [1,13], sex [13,22,23], geographical features factors [6,24], population density [5], and trophic resource availability [13]. Moreover, the availability of this conversion factor can be useful in the acquisition of measures that could be missing from the database of measures obtained using a caliper due to, for example, a distraction or forgetfulness of the measurement collectors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, we found that the conversion factor allowed us to get additional parameters which were inserted into the classical biometric database and then analyzed to obtain information about the wildlife population status. These parameters can be correlated with a lot of different features such as age [1,13], sex [13,22,23], geographical features factors [6,24], population density [5], and trophic resource availability [13]. Moreover, the availability of this conversion factor can be useful in the acquisition of measures that could be missing from the database of measures obtained using a caliper due to, for example, a distraction or forgetfulness of the measurement collectors.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we focused on the mandible, but the method can be extended to all cranial parameters or those of different bone structures. The extra data derived from software specific for shape analysis, thanks to the improvement of the biometric databases, can be useful in the applied study to help in management decisions, such as selective hunting activities [13]. While the roe deer mandibular biometric parameters collected for classical biometrical databases did not show any significant difference between sexes [13], this new method highlighted significant differences between sexes in the distance from the mesial marginal of the 3rd molar tooth to the angle of the mandible (MMM-MA).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We used a two-dimensional geometric morphometry approach consisting of a Relative Warp (RW) analysis of landmark data in roe deer fawn mandibles, in a population residing in the Macerata Province (central Italy Apennines). We evaluated the relationship between mandible shape and trophic resources available during autumn and winter-the most critical feeding period for this species [29]-with the aim to contribute to the development of reliable monitoring tools for informing wildlife management strategies.…”
Section: Introductionmentioning
confidence: 99%